Study of Anti-cholangiocarcinoma and Evaluation of Toxicity of Kaempferia galanga Linn. Rhizome Extract In-vitro as well as In-vivo - Amuamuta, Asmare; Plengsuriyakarn, Tullayakorn; Na-Bangchang, Kesara (Achievements and Challenges of Medicine and Medical Science Vol. 1, 2024)
Background: Cholangiocarcinoma (CCA) is a significant public health problem in many tropical and subtropical parts of the world. Chemotherapy against CCA is mainly ineffective, and the discovery and development of effective chemotherapeutics is urgently needed. This study was conducted to evaluate the safety and anti-CCA activity of ethanolic extract preparation from Kaempferia galangal (K. galanga) Linn. Methods: The ethanolic extract of K. galanga L. rhizome and the standard anticancer drug 5-fluorouracil (5-FU) were evaluated for cytotoxic activity in vitro against the CCA cell line CL-6 using MTT cell proliferation assay. An acute toxicity test (single oral administration with 5,000mg/kg body weight) and subacute toxicity test (daily oral dose of 1,000, 3,000 and 5,000 mg/kg body weight for 28 days) were conducted on ICR mice. To evaluate the anti-CCA activities, the extract preparations of K. galanga L. and 5-FU were also administered orally to normal and CCA xenograft-induced BALB/c nude mice. Results: Mean (SD) inhibitory concentration by 50% (IC50 value) of K. galanga extract and 5-FU against CL-6 in vitro was 64.2 (52.21-89.46) and 107.1 (85.42-122.34) µg/mL, respectively. The results of acute toxicity showed no signs of toxicity. Subacute toxicity study indicated that oral administration of K. galanga extracts up to 1,000 mg/kg did not produce alterations in toxicity (gross appearance and histopathology, hematology and serum biochemistry) in the test groups compared to the control. The ethanolic extract at high (1,000 mg/kg body weight) and medium (500 mg/kg body weight) dose levels and 5-FU showed significant anti-tumor effects concerning tumor volume progression inhibition against xenografts of human CCA growing in nude mice. Conclusion: K. galanga was safe up to the oral dose of 1,000 mg/kg body weight in mice with significant anti-CCA activity.